Capital Fundamentalism and Structural Transformation - Achmad Tohari; Christopher Parsons; Anu Rammohan (Institute of Labor Economics (IZA), 2021)
We revisit the role of Capital Fundamentalism, in the context of the Government of Indonesia's Inpres Desa Tertinggal (IDT or Left Behind Village) Program, which injected capital into poor village economies. We evaluate the impact of the program on village welfare and structural transformation adopting a (fuzzy) regression discontinuity design, which exploits village eligibility for identification. Welfare increased in rural as opposed to urban villages in Java, Sumatra and Bali and Nusa Tenggara, as households exited agriculture in favor of more productive activities in construction, industry and trade. We find no evidence that the program affected structural transformation or welfare in Kalimantan, Sulawesi or Papua, which suggests that structural transformation is a necessary condition for capital injections to foster village development.
Keywords: L16; H53; H54; E22; O10; O18; I38; 330; capital fundamentalism; structural transformation; government intervention; welfare